Peningkatan Penguasaan Tata Bahasa Prancis melalui Model Inkuiri pada Mahasiswa Semester 3 Prodi Bahasa Prancis Universitas Lampung - Kusrini, Nani; Rosita, Diana (FKIP Universitas Lampung, 2017)
Improved mastery of French Grammar through Inquiry Model on Third Semester Students of French Departement of Unila. As grammar is important, an appropriate learning model allowing to increase student’s mastery in grammar is needed. Inquiry models can not only involve learners maximally in the learning process, because they are placed as subjects in it, but this discovery-oriented method also trains participants to develop their intellectual mentality by finding themselves, in this context, the rules of grammar they learn so they can understand and remember better. Keywords: language teaching, French grammar, inquiry model, discovery learningDOI: http://dx.doi.org/10.23960/jpp.v7.i2.201701